Assistência odontológica para idosos durante a pandemia da COVID-19: Uma perspectiva brasileira (Research, Society and Development, 2021)
Aim: This study evaluated the need for dental assistance of elderly people during the COVID-19 outbreak. Methodology: This online observational survey included Brazilian elderly aged ≥ 60 years, with internet access from all Brazil's regions. They completed questionnaires regarding sociodemographic characteristics, general health, COVID fear (scale FCV-19S), and dental assistance. Data were tabulated and analyzed using descriptive and inferential analysis (α = 5%). Results: Overall, 705 elderly people completed the questionnaire. Most volunteers needed dental assistance (58.6%) although only 31.3% visited a dental office, reporting a dental urgency. Elderly had elective appointments (96.3%) in private dental services (95.9%), mostly accompanied during dental assistance (81.6%), without the need to wait (50.7%). Prosthodontic and restorative interventions were the most required procedures. In the dental office, the fear of being contaminated by COVID-19 existed in 53.9%, while the risk of being contaminated was considered medium (46%). Elderly from Northern, Northeastern, and Central-Western, with low educational level, previous COVID-19 diagnosis, and with highest FCV-19S scores had more fear of contamination in the dental office (all p